All in One Multifunctional Perovskite Material for Next Generation SOFC. (1st March 2016) - Dong, Wenjing; Yaqub, Azra; Janjua, Naveed K.; Raza, Rizwan; Afzal, Muhammad; Zhu, Bin
Abstract: Multifunctional roles of La0.2 Sr0.25 Ca0.45 TiO3 (LSCT) perovskite material as anode, cathode, and electrolyte for low temperature solid oxide fuel cell (LT-SOFC) are discovered for the first time, and have been investigated via electrochemical impedance spectroscopy (EIS) and fuel cell (FC) measurements. LSCT resistance decreases prominently in FC environment as shown in this study. An improved performance was observed by compositing LSCT with samaria doped ceria (SDC) at 550 °C when the FC power density increased from tens of mW cm −2 for the pure LSCT system up to hundreds of mW cm −2 . The improved conductivity of LSCT–SDC composite is highlighted. The multifunctionality of LSCT as cathode, anode and electrolyte could be attributed to different conducting behavior at high and low oxygen partial pressures and ionic conduction at intermediate oxygen partial pressures. These new discoveries not only indicate great potential for exploring multifunctional perovskites for the next generation SOFC, but also deepen SOFC science and develop new technologies.